Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs. Swasta Miftahul Falah Sunggal Kabupaten Deli Serdang - Ahmad Ibrahim Hasibuan; Mustapid Mustapid; Candra Wijaya (Universitas Negeri Medan, 2019)
The quality of education should be able to produce skilled graduates, capable of being in accordance with their level of education, honest and most importantly, good morals. Improving the quality of education that is more qualified, among others, through the development and improvement of curriculum and evaluation systems, improvement of educational facilities, development and procurement of teaching materials, and training for teachers and other education personnel. The purpose of this study is to find out what the madrasa principals do at MTs. Private Miftahul Falah Diski. The method used in this study is a qualitative method with a descriptive analysis approach that is a research method that produces descriptive data in the form of written or oral words from people as research objects and observable behaviors so that they are detailed from a phenomenon under study. Based on the results of the study it was found that the leadership carried out by the head of the madrasa in MTs. Private Miftahul Falah Diski is classified into the type of democratic leadership in which the head of the madrasa always holds deliberations to the entire board of teachers, staff and administration in determining each decision to be made. Quality of education in MTs. Private Miftahul Falah I have fulfilled 8 National Education Standards, and it is evidenced by the accreditation of MTs Private Miftahul Falah with the accreditation of B.